Nursing team knowledge about transfusion reactions (Research, Society and Development, 2023)
Identify the nursing team's knowledge about hemotherapy and transfusion reactions. This is a descriptive, field and quantitative study, with the participation of 69 nursing professionals working in an adult intensive care unit and medical/surgical clinic. Data collection was carried out with two questionnaires prepared based on the literature. The data were analyzed by descriptive and relative frequency and the questions that assessed the team's knowledge were dichotomized into correct and incorrect answers; The professional's knowledge was considered sufficient when it achieved a percentage greater than 70% of correct answers. Only 69.6% of professionals had knowledge considered sufficient; 98.6% stated that blood typing is necessary before transfusion; 82.6% highlighted O negative blood as a universal donor; 95.7% of nursing professionals were able to identify the signs and symptoms present in transfusion reactions, with a predominance of fever (91.3%), malaise (87%), chills (65.2%) and nausea (56. 5%). However, only 55% of professionals received training on transfusion reactions. It is reiterated that the majority of professionals have assertive knowledge about hemotherapy, however, there is a need for reflection and awareness among institutional managers regarding the provision of ongoing education on the subject.